An Interesting Case of a Large Cystic Mesothelioma of the Omentum in a Pediatric Patient - Periyasamy, Gnanasekar; Kumarasamy, Sivasundhar; Sekhar, Karumuri Srinivas; Vaithyanathan, Malathi; Sengottaiyan, Saravanakumar; Shanmugasundaram, Saravanan Thangam; Gnanasambandam, Kumaragurubaran (Journal of Gastrointestinal and Abdominal Radiology, 2019)
We present an interesting case of a large intra-abdominal cystic lesion in a 14-year-old girl who presented with abdominal discomfort and pain. The patient was evaluated with magnetic resonance imaging (MRI) and found to have a large septated cystic lesion arising from the gastrohepatic omentum. She underwent surgery, and the diagnosis of cystic mesothelioma was confirmed in the histopathology. To the best of our knowledge, only a few cases of benign omental mesothelial cysts have been reported.
Keywords: omental cyst; mesenteric cyst; mesothelioma